Pengaruh Citra Merek, Harga, Kualitas Produk Terhadap Loyalitas Pelanggan dengan Kepuasan Konsumen sebagai Variabel Intervening (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2023)
This research is a study of the effect of brand image, price and product quality on customer loyalty with consumer satisfaction as an intervening variable on Miniso brand. The purpose of this research is to find out whether the variables of brand image, price and product quality affect customer loyalty through the intervening variable, namely customer satisfaction. In this study it is known that product quality at the Miniso brand has a strong influence on customer loyalty through customer satisfaction. The research method used is path analysis method. While the samples in this study were withdrawn using a purposive sampling method with a total sample of 100 respondents taken from the consumer population of the Miniso brand. The results of the Sobel test show that brand image and price have no effect on customer loyalty with consumer satisfaction as intervening variables where both have t count values less than t table. Product quality has an influence on customer loyalty with customer satisfaction as an intervening variable, this is because the calculated t value is greater than the t table value. Brand image has no effect on customer loyalty. Price, product quality and consumer satisfaction have an influence on customer loyalty. Companies must be able to maintain and provide good product quality to create a sense of satisfaction in consumers and make consumers loyal.